Thermodynamic Formulations of Excess and Absolute Values of Adsorption on Solid Surfaces: A Comparison of One- and Two-Phase Approaches - H. Wittkopf; P. Bräuer (Adsorption Science & Technology)
The generally used methods of thermodynamic adsorption analysis are summarized in two basic concepts: the two-phase approach (which is an adequate picture of volume phase thermodynamics in adsorption) and the one-phase approach (which uses excess values for the thermodynamic description of adsorption). Differential and integral molar values of adsorption Δ a X̄ and Δ a X in the two-phase approach are not identical with the corresponding excess values Δ a X̄ s and Δ a X s in the one-phase approach. Especially at high temperatures and high pressures they may be entirely different. It is shown that the experimental methods most usually in adsorption thermodynamics (as adsorption volumetry and gravimetry) give excess data which are to be used in the one-phase approach but which can be transformed to the two-phase approach. Using statistical thermodynamic calculations the difference between these basic concepts is shown over a wide temperature range for the first virial coefficient, the internal energy and the heat capacity of adsorption.